2021
DOI: 10.1016/j.adro.2020.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perspectives and Concerns for the 2020 to 2021 Radiation Oncology Interview Season

Abstract: Purpose: Recently, the Coalition for Physician Accountability Work Group on Medical Students in the Class of 2021 recommended limiting visiting medical student rotations, conducting virtual residency interviews, and delaying the standard application timeline owing to the ongoing corona virus disease 2019 (COVID-19) pandemic. These changes create both challenges and opportunities for medical students and radiation oncology residency programs. We conducted a comprehensive needs assessment to prepare for a virtua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 15 publications
0
13
0
1
Order By: Relevance
“…Although several recent surveys have found virtual interviews to be a challenging way for applicants to learn about the culture of a program and obtain deeper insight into the training offered, virtual interviews do offer distinct advantages for convenience and eliminating travel costs, allowing applicants to schedule multiple interviews in a short span of time. 19 , 20 In a recent survey of 1,711 medical students, Seifi et al 21 reported that although most medical students prefer in-person interviews, most medical students also believe that virtual interviews should still remain an option for applicants. As such, although virtual interviews were a necessity during the pandemic, it is possible that some programs may still preserve the option of virtual interviews in future years.…”
Section: Discussionmentioning
confidence: 99%
“…Although several recent surveys have found virtual interviews to be a challenging way for applicants to learn about the culture of a program and obtain deeper insight into the training offered, virtual interviews do offer distinct advantages for convenience and eliminating travel costs, allowing applicants to schedule multiple interviews in a short span of time. 19 , 20 In a recent survey of 1,711 medical students, Seifi et al 21 reported that although most medical students prefer in-person interviews, most medical students also believe that virtual interviews should still remain an option for applicants. As such, although virtual interviews were a necessity during the pandemic, it is possible that some programs may still preserve the option of virtual interviews in future years.…”
Section: Discussionmentioning
confidence: 99%
“…The cut-off and threshold of delaying cancer treatment and screening will also vary based on geographical capabilities and local burden of COVID-19 cases and the phase of the pandemic ( Everett et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Culture is also a recurring keyword within the articles for two reasons, some of the articles are related directly to digital cultural heritage applications [12]. However, in other cases the works refer to the need to virtual conference tools to embrace a solution for the lack of workplace culture when working from home, particularly for medicine education [20]. It is, of course, a challenge to recreate a workplace culture within a digital setting, or recreate a learning culture that a student would find typically in a physical classroom environment.…”
Section: Discussionmentioning
confidence: 99%